2019
DOI: 10.3390/ani9030087
|View full text |Cite
|
Sign up to set email alerts
|

Summer Savory (Satureja hortensis L.) Extract as Natural Feed Additive in Broilers: Effects on Growth, Plasma Constituents, Immune Response, and Ileal Microflora

Abstract: This study investigated the effects of summer savory (Satureja hortensis L.) extract (SSE) on growth, plasma constituents, immune response, and gut microbiota of broiler chickens. A total of 300 day-old broiler chicks were randomly assigned to five dietary treatments containing five replicates of 12 birds each. The treatments consisted of a controldiet without feed additive and experimental diets supplemented with four levels of SSE (100, 200, 300, and 400 mg/kg, respectively). Results showed no significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The issue considering antibiotic resistance has created an augmented force to reduce antibiotic uses in livestock and poultry production [1,2]. Dietary inclusion of herbs and their extracts has growth-promoting roles in poultry [3]. Furthermore, different natural medicinal plants and their extracts as feed supplements have been used as a substitute for antibiotics in poultry production [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The issue considering antibiotic resistance has created an augmented force to reduce antibiotic uses in livestock and poultry production [1,2]. Dietary inclusion of herbs and their extracts has growth-promoting roles in poultry [3]. Furthermore, different natural medicinal plants and their extracts as feed supplements have been used as a substitute for antibiotics in poultry production [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the continuous and over application of in-feed antibiotics in poultry production has created public health hazards [2]. Movahhedkhah et al [3] reported that application of natural herbs and their extracts has growth-enhancing roles in chickens. Due to huge economic losses by gastrointestinal infections and of strict laws to apply in-feed antibiotics, there is a demand for a natural alternative therapeutic agent [4].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are usually used in poultry for therapeutic, preventive, and nutritional purposes [1][2][3]. Using antibiotics for the growth promotion or prevention and treatment of infectious diseases can result in resistance among both resident bacterial pathogens and commensal organisms [4,5].…”
Section: Introductionmentioning
confidence: 99%